Medicolegal Death Investigators a Profession That Could Contribute to Criminal Justice System - Çetin, Volkan (The Bulletin of Legal Medicine, 2014)
In the field of forensic medicine, it is essential for a forensic pathologist to gather as much information as possible, about the case in order to assign a cause and manner of death. The flow of information to the forensic pathologist is expected to be expeditious, accurate and adequate. In this article, it is aimed to introduce a profession, Medicolegal Death Investigators, who work in Medical Examiner Offices in the United States. Their duties and responsibilities in the system will be described in details. Because of their contributions to crime scene investigations, implementing a similar approach in the medico-legal investigations in Turkey will be proposed; the necessity and benefits will be discussed.Keywords: Medicolegal Death Investigators; Crime Scene Investigations.
Keywords: medicolegal death investigators; crime scene investigations